Cancer vaccine: how far are we from curing cancer?. (1st February 2019) - Choudhury, Ruhul; Durrant, Lindy
Abstract : Although cancer treatment has developed considerably in the 21st century, there are still 8–9 million people dying of this disease each year. One strategy, using a patient's own immune system to combat their cancer, has recently led to a significant improvement in survival rates. The concept of immunotherapy is not new; as far back as 1893, William Coley reported tumour regression following repeated injections of bacterial toxin from Streptococcus pyogenes in a patient with advanced sarcoma. Over 100 years later, the use of cancer vaccine has come a long way, with a better understanding of the immune system's interaction with the tumour microenvironment.